2020
DOI: 10.1002/cbf.3576
|View full text |Cite
|
Sign up to set email alerts
|

Potential small‐molecule drugs as available weapons to fight novel coronavirus (2019‐nCoV): A review

Abstract: Since the new coronavirus known as 2019‐nCoV (severe acute respiratory syndrome coronavirus 2, SARS‐CoV‐2) has widely spread in Wuhan, China, with severe pneumonia, scientists and physicians have made remarkable efforts to use various options such as monoclonal antibodies, peptides, vaccines, small‐molecule drugs and interferon therapies to control, prevent or treatment infections of 2019‐nCoV. However, no vaccine or drug has yet been confirmed to completely treat 2019‐nCoV. In this review, we focus on the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The benefit of these therapies is that, since they have been approved for the treatment of other viral infections, their metabolic properties, dosages used, possible effectiveness and side effects are known. However, because these therapies are broad-spectrum, they are unable to directly kill CoVs, and potential side effects should be considered ( 144 ). Unfortunately, due to differences in pharmacokinetic (PK) and pharmacodynamic (PD) properties, in vitro analysis seldom translates to in vivo , posing a significant barrier to clinical translation of a therapeutic candidate ( 145 ).…”
Section: Therapeutics Strategiesmentioning
confidence: 99%
“…The benefit of these therapies is that, since they have been approved for the treatment of other viral infections, their metabolic properties, dosages used, possible effectiveness and side effects are known. However, because these therapies are broad-spectrum, they are unable to directly kill CoVs, and potential side effects should be considered ( 144 ). Unfortunately, due to differences in pharmacokinetic (PK) and pharmacodynamic (PD) properties, in vitro analysis seldom translates to in vivo , posing a significant barrier to clinical translation of a therapeutic candidate ( 145 ).…”
Section: Therapeutics Strategiesmentioning
confidence: 99%
“…COVID-19 and its associated mucormycosis impair the immune system by initiating the cytokine storm in such patients. MSC-based therapy is coming up with new hope for promoting endogenous repair and inhibiting the cytokine storm, hence, helpful in managing COVID-19 and its associated mucormycosis ( Rahimkhoei et al, 2021 ). In a previously conducted study on COVID-19 patients, injection of MSCs to lungs in pulmonary disease showed a protective effect on the endothelial cells ( Liang et al, 2020 ).…”
Section: Msc-based Management Of Covid-19–associated Mucormycosismentioning
confidence: 99%
“…Although the clinical effectiveness of these drugs has not yet been proven for COVID‐19, more recent studies show that some drugs may be potential drugs for COVID‐19 treatment. These potential drugs include lopinavir/ritonavir, nucleoside analogs, neuraminidase inhibitors, remdesivir, umifenovir, DNA synthesis inhibitors (tenofovir disoproxil, lamivudine), chloroquine/h ydroxychloroquine , hydroxychloroquine+azithromycin, ACE2‐based peptides, 3C‐like protease (3CLpro) inhibitors 32,120‐129 …”
Section: Potential Treatment Agents For Covid‐19mentioning
confidence: 99%